SPATIO -TEMPORAL VARIATIONS OF MACROBENTHIC INVERTEBRATES IN RELATION TO PHYSICO-CHEMICAL PARAMETERS OF BOTTOM SEDIMENTS IN AN URBAN EUTROPHIC LAKE - Paramita Banerjee Sawant; Chandra Prakash; N. K. Chadha; A. K.Jaiswar; S. Dam Roy; Soniya Sukumaran; Aritra Bera; Bhawesh T. Sawant; Sujitha Thomas (Journal of Indian Fisheries Association, 2018)
ABSTRACT"The spatio-temporal vartations of macrobenthicinvertebrates in relation to physico-chemical parameters of bottom sediments were studied in an urban eutrophic lake (Naushad All sarovar, Maharashtra, popularly known as Powal lake], Out of 15 species of macrobenthic invertebrates recorded from 5 classes, highest number of individuals square metre (m'), belonged to Class Insecta (11046), followed by Gastropoda(11666). Polychaeta (6712) and Oligochaeta (4293), and Maxillopoda (576). Species diversity was highest and lowest during post monsoon and monsoon, respectively, whereas, highest and lowest biomass were recorded in monsoon (7.41 gm ) and pre monsoon, (0,72-1.53 g m J, respectively. Higher number of individuals recorded during pre monsoon and post monsoon could be correlated to high percentage of organic carbon in lake sediments (2.44 - 3.0896). Tipula sp and Chironomus sp. (bioindicators of arganic pollution) were mast dominant. Presence of Limnodrilus sp falso a biaindicator of pollution] in all seasons at fifth station, was significant.Regression analysis indicated % silt and organic carbon as the most important factors influencing seasonal pattern of macrobenthic invertebrates. Cluster Analvsis and Non parametrie multidimensional scaling (MDS), showed distinct clustering of stations 4 and 5 in terms of abundance of macrabenthic invertebrates. further confirming their organically polluted macore. Prancipal Component Analysis (PCA) yielded 4 components, where factor loadings indicated maior environmental factors as temperature of (air and water), dissolved axygen, pll, carbon dioxide and water hardness.